Elevated serum miR-142-5p correlates with ischemic lesions and both NSE and S100β in ischemic stroke patients - Xu WeiWei; Cheng YongXia; An Ning; Jiang MeiLing (Open Medicine)
This study aims to evaluate the correlation between miRNAs and known nerve injury markers neuron-specific enolase (NSE) and S100β in ischemic stroke (IS) patients, exploring its efficacy.